Strategi Guru dalam Menyusun Soal Evaluasi Matematika Berbasis HOTS pada Siswa Kelas 6 SDN Kalideres 06 Pagi - Huliatunisa, Yayah; Saputra, Tio; Sulistiyani, Putri Salsabilla; Ramadhanty, Salma; Fauziah, Putri; Rahmanda, Farah Putri (MASALIQ, 2022)
Higher Order Thinking Skills (HOTS) is something that requires teachers to play an active role in constructing students' understanding towards complex thinking processes. The application of HOTS in the preparation of math problems requires teachers to apply various strategies. This study aims to analyze the teacher's strategy in compiling math problems based on HOTS (Higher Order Thinking Skills) in Class VI students at SDN Kalideres 06 Pagi, using descriptive qualitative methods with a case study approach. The sixthgrade teacher was used as a data source. Data collection techniques through observation, documentation and interviews. The results of the data obtained were analyzed through data reduction activities, data presentation, and drawing conclusions, which were then tested for data validity using source triangulation. The results showed that the teacher implemented a strategy in an effort to improve his ability in preparing HOTS-based mathematics evaluation questions through the intensity of participation in training and development regarding the preparation of HOTS-based evaluation questions, as well as providing motivation, stimulus, and intensive guidance to students in working on HOTS-based math problems.